Susceptibility of The Asian Corn Borer, Ostrinia furnacalis, to Bacillus thuringiensis Toxin CRY1AC - Aye Kyawt Kyawt Ei; Y. Andi Trisyono; Witjaksono Witjaksono (Universitas Gadjah Mada, 2008)
The larval susceptibility of the Asian corn borer, Ostrinia furnacalis (Guenee) (Lepidoptera: Crambidae), to a Bacillus thuringiensis protein (Cry1Ac) was evaluated using insect feeding bioassays. The founding population of O. furnacalis was originally collected from the experimental station of UGM at Kalitirto and had been reared in the laboratory for three generations using an artificial diet “InsectaLf”. The tested instars were exposed on diets treated with a series of concentrations of Cry1Ac for one week. The LC50 values on the seventh day after treatment for 1st, 2nd, 3rd and 4th instars were 7.79, 21.12, 113.66, and 123.17 ppm, respectively, showing that the higher the instars the lesser the susceptibility to Cry1Ac. When the neonates were exposed to sublethal concentrations of Cry1Ac (0.0583, 0.116, and 0.5830 ppm), growth and development of the surviving larvae were inhibited. The fecundity and viability of females produced from treated larvae decreased with increasing the concentrations. These findings indicate that Cry1Ac is toxic to larva of O. furnacalis and has chronic effects to larvae surviving from Cry1Ac ingestion.